Analysis Of Risk Management In Development SMK Stikes Rajawali Bandung (Case Study: Well Foundation) - Firda Aulia Khairin; Annisa Annisa (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
The SMK STIKES Rajawali Bandung project is a unique project because it has a steep terrain location that creates various risks, so a risk analysis is needed. The identification in this study was 32 risks. This research uses qualitative and quantitative methods with the stages of identifying possible risks, assessing risks, knowing the causes, and ways of dealing with dominant risks if they occur. The results of the study of the 32 risks consisted of 3 very high risks, 2 high risks, 23 medium risks and 4 low risks. The biggest risk comes from the external risk that can be detected, namely the risk of rain with a score of 20. Therefore, the risk of rain requires ideal treatment using a dewatering pump.